Energy Efficient Cities : Assessment Tools and Benchmarking Practices. - Bose, Ranjan K. (Marseilles Symposium., 2010)
Energy is intrinsic to urban settlements, embedded in the built environment, and directly used to power socio-economic activity, transport and communications, and enable the provision of municipal services. In response to the crucial role of urban energy efficiency for environmentally sustainable and inclusive development processes, ESMAP?s Energy Efficient Cities Initiative (EECI) was launched in October 2008 to facilitate the implementation of practical energy solutions that meet the development priorities of cities, and simultaneously build their climate resilience. Chapter 1 begins with a.